CHARACTERISTICS OF TUMORS THAT DEVELOPED IN MICE AFTER TREATMENT WITH IRRADIATED SYNGENEIC MESENCHYMAL STEM CELLS OF BONE MARROW - Moskaleva, E Yu; Zhorov, E S; Semochkina, Yu P; Rodina, A V; Vysotskaya, O V; Glukhov, A I; Chukalova, A A; Posypanova, G A; Saprykin, V P (T͡S︡itologii͡a, 2017)
Mesenchymal stem cells (MSCs) are present in almost all organs and tissues of the organism. It is believed, that MSCs could be transformed into cancer stem cells spontaneously or under influence of genotoxic factors and trigger the growth of tumors. The aim of this work was to study the possibility of malignant transformation of cultured MSCs from murine bone marrow (MSCs-BM) after g-irradiation in vitro and characterize of biochemical and histological features of the tumors that developed after transplantation of MSCs-BM into syngeneic mice. Tumors were observed in 3—4 months after MSCs-BM transplantation. After administration of MSCs-BM irradiated at a dose of 1 Gy, tumors were seen in 2 of 5 mice. After transplantation of MSCs-BM irradiated at a dose of 6 Gy, tumors were found in all 5 of 5 mice. In the case of control MSCs-BM, only one tumor appeared in 6 months after transplantation. The telomerase activity was two times higher in the tumor developed from 6 Gy irradiated MSCs-BM than from 1 Gy irradiated MSCs-BM. The tumors developed from control and irradiated MSCs-BM were classified as multicomponent mesenchymomas («mixture of sarcomas»). Histological examination showed that tumors contained tissue areas of different histogenesis. Thus, MSCs-BM g-irradiated at doses of 1 and 6 Gy and, much less frequently, control MSCs-BM can transform into tumor cells and induce development of multicomponent mesenchymomas.